Fixed Point Theorems for Generalized αs-ψ-Contractions with Applications - Zhenhua Ma; Muhammad Nazam; Sami Ullah Khan; Xiangling Li (Journal of Function Spaces)
We study the sufficient conditions for the existence of a unique common fixed point of generalized αs-ψ-Geraghty contractions in an αs-complete partial b-metric space. We give an example in support of our findings. Our work generalizes many existing results in the literature. As an application of our findings we demonstrate the existence of the solution of the system of elliptic boundary value problems.